Antler casting in relation to parturition in semi-domesticated female reindeer - Reimers, Eigil; Nieminen, Mauri; Tsegaye, Diress (Rangifer, 2013)
We investigated the timing of the right and left antler casting in semi-domesticated reindeer (Rangifer tarandus tarandus L.) in relation to parturition using 139 antlered adult individually marked females in 2008-09 between May 5 and June 2; a period when all calves were born and all females cast their antlers. We analysed time of casting of right and left antler in relation to pregnancy, female age and body weight, weight and sex of the calf, and birth date. Seven of the females were non-pregnant (barren) and cast their antlers during the second week of May and at the same time as some of the females that gave birth initiated antler casting. Postpartum retention of antlers varied from 0 to 15 days. We found no difference between left and right antler casting schedule and within two days apart, 91% of the females had cast both antlers. The maximum number of antler castings per day occurred on the seventh day after parturition. Of the 132 females that gave birth, 7 females (5.3%) cast both antlers 5 – 23 days before calving, three females cast right antler 6 – 10 days before and the left antler 2 – 5 days after calving and one female that bore only a left antler casted a day before calving. Antler casting among lactating females was related only to female age, indicating that older females cast antlers earlier than younger females (i.e. 3 days earlier than the pooled mean of 7.6 days). Apart from calving date being two days later among the 7 females that alternated their casting schedule, female body weights, calf sex and calf birth weight among them did not differ between the two years. We conclude that it is a small but consistent antler casting overlap between barren and pregnant/lactating females, indicating that the control mechanism for casting of antlers is not “fool proof” and that antler status prior to parturition does not accurately predict pregnancy status in this domestic reindeer group.